Challenging Cough Cases: A New Frontier in Otolaryngology. (23rd August 2013) - Altman, Kenneth W.; Krouse, John H.; Luong, Amber U.; Carroll, Thomas L.; Merati, Albert L.
Abstract : Program Description: Otolaryngologists are playing an increasingly important role in the evaluation and treatment of patients with chronic cough. This miniseminar will involve the use of challenging case presentations, panel discussion, and audience participation to emphasize evidence‐based practice and the "state‐of‐the‐art" for patients with chronic cough. Controversial areas will include the concept of prioritization and use of evidence‐based protocols, the importance of early diagnosis in value‐based healthcare, and basic science mechanisms for inter‐relatedness of aerodigestive disease. Also, the costs of care, time to diagnosis and resolution, and underlying risks to the patient will be addressed. Educational Objectives: 1) Use evidence‐based treatment guidelines in the evaluation and treatment of chronic cough. 2) Recite the spectrum of common and uncommon causes with an appreciation of the basic science mechanisms. 3) Evaluate these complex patients, perform a procedure‐oriented evaluation, and prescribe appropriate pharmacotherapy at their home institution.